PACIOLO AND MODERN ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1928)
Abstract The appearance a few years ago of a new English translation of Frater Lucas Paciolo's book "De Computis et Scripturis'" raises the question a new of how much, or how little, the art of bookkeeping has changed in the 434 years since 1494 when bookkeeping's first printed book appeared. But one should not open Paciolo's book with the expectation of finding modern practices completely foreshadowed. Nineteenth and twentieth century conditions have, of course, brought about many modifications of what was originally sound method, and have, in some cases, forced the introduction of practices which are of necessity entirely foreign to fifteenth century conditions. From the very beginning certain basic peculiarities of method and form have been associated with bookkeeping. These fundamental characteristics still persist, and, being peculiar to double-entry bookkeeping, form the principal means of setting it apart from other fact-manipulating systems. Ever since the record-keeping methods of bankers and governments were expanded to suit mercantile affairs, bookkeeping has possessed a characteristic theory, a characteristic form, and a characteristic technology.